2022
DOI: 10.1097/md.0000000000029172
|View full text |Cite
|
Sign up to set email alerts
|

Traction method versus conventional endoscopic submucosal dissection for gastric epithelial neoplasms

Abstract: Introduction: Endoscopic submucosal dissection (ESD) is an advanced therapeutic technique for en bloc resection of superficial gastrointestinal neoplasms. Although gastric ESD is minimally invasive and provides favorable outcomes, it is technically difficult and requires a long procedure time for dissection. The traction-assisted approach overcomes some of the difficulties of gastric ESD, but its ability to reduce the procedure time remains unclear. The traction-assisted approach using dental floss and a clip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…The increased number of publications on the traction-countertraction issue in flexible endoscopy in recent years could reflect a lack of this function in current available endoscopic instruments [20][21][22][23][24][25][26]. During high-end therapeutic endoscopies such as ESD, traction may be necessary on the gut wall or the specimen, which can be solved using the demonstrated instruments, such as the Endo-dissector and/or the EINTS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased number of publications on the traction-countertraction issue in flexible endoscopy in recent years could reflect a lack of this function in current available endoscopic instruments [20][21][22][23][24][25][26]. During high-end therapeutic endoscopies such as ESD, traction may be necessary on the gut wall or the specimen, which can be solved using the demonstrated instruments, such as the Endo-dissector and/or the EINTS.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic experts may get by without these options since they can compensate for this lack with their vast experience. For "average" endoscopists, this limitation of optimal instrument function may be critical, and the literature provides some examples of instrument optimization regarding interventional endoscopic procedures [19][20][21][22][23][24][25][26]. Several attempts were reported to create additional assisting instruments using external tools other than the regular endoscope, based on a more surgical paradigm, to facilitate endoscopic procedures [19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric endoscopic submucosal dissection (ESD) for lesions of the greater curvature of the gastric body is challenging owing to difficulty in approaching the lesion, submersion 1 , and vertical confrontation with the lesion. Threaded-clip traction attached to the lesion is widely used in gastric ESD 2 3 .…”
Section: Figmentioning
confidence: 99%
“…Clip-line assisted ESD has been reported to significantly shorten procedure time without compromising safety while performing resection of gastric lesions ( 27 ). Further prospective, randomized and controlled study of this technique revealed that the procedure time reduction is most pronounced when performing ESD in the greater curvature of the upper or middle stomach with a low risk of perforation ( 28 ).…”
Section: Traction By Locationmentioning
confidence: 99%